2023
DOI: 10.1002/wps.21069
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive behavior therapy vs. control conditions, other psychotherapies, pharmacotherapies and combined treatment for depression: a comprehensive meta‐analysis including 409 trials with 52,702 patients

Abstract: Cognitive behavior therapy (CBT) is by far the most examined type of psychological treatment for depression and is recommended in most treatment guide­lines. However, no recent meta‐analysis has integrated the results of randomized trials examining its effects, and its efficacy in comparison with other psychotherapies, pharmacotherapies and combined treatment for depression remains uncertain. We searched PubMed, PsycINFO, Embase and the Cochrane Library to identify studies on CBT, and separated included trials… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(61 citation statements)
references
References 42 publications
(52 reference statements)
2
40
0
Order By: Relevance
“…[18] Psychotherapy should be considered as alternative treatment especially for long-term users, as recent meta-analyses indicate that psychotherapy is superior in longer treatment than AD treatment alone. [39,40] Our results show that long-term users across all age categories are more likely receiving psychiatric or psychotherapeutic care compared to medium-and short-term users. However, one third of long-term users did not receive psychiatric and psychotherapeutic care, which requires further investigations into the underlying reasons.…”
Section: Discussionmentioning
confidence: 71%
“…[18] Psychotherapy should be considered as alternative treatment especially for long-term users, as recent meta-analyses indicate that psychotherapy is superior in longer treatment than AD treatment alone. [39,40] Our results show that long-term users across all age categories are more likely receiving psychiatric or psychotherapeutic care compared to medium-and short-term users. However, one third of long-term users did not receive psychiatric and psychotherapeutic care, which requires further investigations into the underlying reasons.…”
Section: Discussionmentioning
confidence: 71%
“…Task sharing in primary health care is vital to increase treat ment coverage for people in need, but it rarely includes providing evi dence based psychological interventions. Yet research shows that cognitive behavioral therapy (CBT), on its own or combined with antidepressants, is the first line treatment for adult depressive dis orders 2 . CBT is also first line treatment for other conditions, includ ing anxiety disorders.…”
Section: Putting Psychological Interventions First In Primary Health ...mentioning
confidence: 99%
“…In the Japanese population, the estimated numbers of inpatients and outpatients with depression in 2020 were 280,000 and 910,000 patients, respectively [ 2 ]. For those with depression, non-invasive or non-pharmacological therapeutic approaches such as exercise therapy [ 3 ], cognitive behavior therapy [ 4 ], and psychoeducation [ 5 ] are recommended clinically. Therapeutical approaches targeting specific symptoms of depression, such as night-sleep disorder and low physical activity levels in daily life, were well documented in the last few decades; one study suggested that patients with depression and a low daily physical activity level might have significantly shorter night-sleep times than healthy controls, as well as a significantly low relative amplitude (RA) between physical activity levels during daytime and those during nighttime [ 6 ].…”
Section: Introductionmentioning
confidence: 99%